A Pragmatic analysis of the subject in electronic messages: Are our messages relevant? (Ogigia. Revista Electrónica de Estudios Hispánicos, 2019)
The genre of electronic mail is widespread nowadays in both strictly personal as well as professional or institutional communication. Therefore, those studies that attempt to define its pragmatic peculiarities are especially relevant. In Relevance Theory, cognitive processes triggered by the subjects involved in communicative exchanges are analysed from the assumption that every communicative act conveys the presumption of its own relevance. Relying on this theoretical framework, in this paper we analyse the relationship between the body of the email and the subject, or small statement placed in the message header to introduce and contextualize this kind of text. Taking as a reference the classification of a sample of emails, we will establish a typology of subjects depending on how they contextualize informatively the messages they introduce, that is, how they reveal their presumption of relevance.
Keywords: Electronic mail; subject; pragmatics; relevance theory